(untitled) (Baghdad Science Journal, 2019)
This research included the preparation of 2-mercaptobenzoxazole (N1) by the reaction of ortho-aminophenol with carbon disulfide in an alcoholic potassium hydroxide solution. The 2-mercapto benzoxazole (N1) was then treated with hydrazine to obtain the 2-hydrazino benzoxazole (N2). A number of hydrazones (N3-N5) were prepared through the reaction of N2 with different benzaldehydes. The compound (N6) was also prepared whereby the ring closing of hydrazone (N3) using chloroacetylchloride, while the compound (N7) was prepared by treating 2-hydrazino benzoxazole with acetylacetone. When the compound (N1) was treated with formaldehyde, it afforded the compound (N8). Also, the N9 was obtained from the reaction of N1 with chloroacetic acid in the presence of alcoholic potassium hydroxide. The prepared compounds were characterized using physico-chemical and spectroscopic methods such as melting point, infrared spectroscopy (IR) and the proton nuclear magnetic resonance (1H-NMR). Thereafter, some of the compounds were selected for in vitro antibacterial activity and one of these compounds showed an inhibition effect against gram positive only which is very important because it is considered as specific antibacterial drug.